The Bidirectional Transfer and Fetal Vascular Pressure Changes Due to the Presence of 125I-Labeled Inhibin A in the ex-vivo Human Placental Model - Roger E. Bawdon; Victor Ghetie (Hindawi Limited, 2003)
Objective: The purpose of this study was to investigate the transport of inhibin A and to determine its effects on fetal vascular pressure at elevated levels in the human placenta using I125 -labeled synthetic glycoprotein.